Bottlenecks in the Transferability of Antibiotic Resistance from Natural Ecosystems to Human Bacterial Pathogens - Martinez, Jose L. (Frontiers in Microbiology, 2012)
It is generally accepted that resistance genes acquired by human pathogens trough horizontal gene transfer have been originated in environmental, non pathogenic bacteria. As the consequence, there exists an increasing concern on the role that natural, non-clinical ecosystems, may play on the evolution of resistance. Recent studies have shown that the variability of determinants that can provide antibiotic resistance upon their expression in a heterologous host is much larger than what is actually found in human pathogens. Along the review, the role that different processes as founder effect, ecological connectivity, fitness costs or second-order selection may have on the establishment of a specific resistance determinant in the population of bacterial pathogens is analysed.